The multicriteria assessment of the spatial planning process: the aspect of investment - Komarovska, Andželika; Ustinovichius, Leonas; Peckienė, Aurelija (Journal of Civil Engineering and Management, 2015)
The effectiveness of an investment determined by the macroeconomic situation of a country stimulates national macroeconomic development. The principles of sustainable development must be followed in order to effectively organize the spatial planning process. To ascertain the efficiency of the legal base of Lithuanian spatial planning, a comparison of the Lithuanian spatial planning organization process with those carried out in Poland and Germany has been performed. For this purpose, the basic principles of spatial planning legislation have been analyzed. The challenge was addressed to the analysis of the verbal spatial planning system. Verbal decision-making system UniComBOS (Unit Comparison for the Best Selection Object) is used for determining a model for an effective spatial planning system. The modified concept of the spatial planning model is suggested in accordance with the results obtained in the run of the carried out analysis.